Utilization of Mangroves as Ecoprint Materials to Support Souvenir Products at the Ngulusenge Mangrove Tourism Attraction, Central Maitara Village, District of North Tidore - Rina, Rina; Abubakar, Salim; Subur, Riyadi; Sabar, Mesrawaty; Sunarti, Sunarti; Abubakar, Yuyun; Al Hadad, M. Said; Fadel, Ariyati H. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Ecoprint is a term that comes from the words